Antioxidant and cytotoxic activities of Ageratum conyzoides stems - Nasrin, Fatema (International Current Pharmaceutical Journal, 2013)
Modern civilization is facing more than hundreds of disorders associated with free radicals and natural antioxidants from non-edible plants are gaining importance to fight these disorders. The intention of this report is to evaluate a well known medicinal weed Ageratum conyzoides stems for its antioxidant and cytotoxic Effects. Antioxidant potentiality of the crude methanolic extract of the Ageratum conyzoides (AC) stems was investigated on DPPH scavenging activity, reducing ability, total antioxidant capacity as well as total phenolic contents. Cytotoxic study was done by brine shrimp lethality bioassay and vincristin sulphate was used as standard. The total phenols and total antioxidant capacity of AC was found to be 38.125 ± 2.01mg/g equivalent of gallic acid and 333.37 ± 4.22mg/gm equivalent of ascorbic acid, respectively. The percentage (%) scavenging of DPPH free radical of the extract was found to be concentration dependent with IC50 value 46.01 ± 2.23µg/ml while IC50 value of standard ascorbic acid was found to be 29.56 ± 0.11?g/ml. The reducing power of AC was found to be concentration dependent. The cytotoxicity exhibited by AC was found promising with LC50 value 1.32?g/ml, comparing with the LC50 (0.689?g/ml) values of vincristin sulphate. The present investigation suggests that Ageratum conyzoides possesses remarkable antioxidant and cytotoxic property. DOI: http://dx.doi.org/10.3329/icpj.v2i2.13195 International Current Pharmaceutical Journal 2013, 2(2): 33-37